Revitalisasi Nilai-Nilai Pai Dalam Menanggulangi Problematika Bullying Pada Siswa Mts Ma’arif Nu 01 Susukan Banjarnegara - Abdullah Khasan; Rifqi Muntaqo; Ali Imron (Institut Nalanda, 2024)
One phenomenon that has attracted public attention in education is violence in schools. Therefore, with the revitalization of Islamic religious education, especially in Aqidah education, human morals will become good individuals and make perfect humans in religious life, society and the state. This thesis aims to: 1) To find out how to revitalize Islamic religious values ​​in overcoming the problem of bullying at Mts Ma'arif NU 01 Susukan Banjarnegara. 2) To find out what forms of bullying occur among students at Mts Ma'arif NU 01 Susukan Banjarnegara. 3) To determine the supporting and inhibiting factors for the revitalization of Islamic religious values ​​in overcoming the problem of bullying at Mts Ma'arif NU 01 Susukan Banjarnegara. This thesis uses a qualitative research approach, namely describing precisely the characteristics of individuals, circumstances, symptoms or groups. Data collection is carried out by means of observation, interviews and documentation so that various valid information and data can be obtained. Revitalization is a strategy used by teachers to overcome the problem of bullying, which uses problem-finding, approach, socialization and motivation strategies.